A Multilevel Model of Team Cultural Diversity and Creativity: The Role of Climate for Inclusion. (4th June 2015) - Li, Ci‐Rong; Lin, Chen‐Ju; Tien, Yun‐Hsiang; Chen, Chien‐Ming
Abstract: We developed a multi‐level model to test how team cultural diversity may relate to team‐ and individual‐level creativity, integrating team diversity research and information‐exchange perspective. We proposed that the team climate for inclusion would moderate both the relationship between cultural diversity and team information sharing and between cultural diversity and employee information elaboration. We collected time‐lagged data from 384 members and their leaders within 57 multicultural work teams. The results showed that team cultural diversity was positively related to both team creativity and individual creativity through team information sharing and employee information elaboration, respectively. We also found that the indirect positive relationship with team creativity and individual creativity was stronger for team cultural diversity when climate for inclusion of multicultural work teams was stronger.